On the sum of gamma random variates with application to the performance of maximal ratio combining over Nakagami-m fading channels - Ansari, Imran Shafique; Yilmaz, Ferkan; Alouini, Mohamed Slim; Kucur, Oğuz (My University, 2012)
The probability distribution function (PDF) and cumulative density function of the sum of L independent but not necessarily identically distributed gamma variates, applicable to maximal ratio combining receiver outputs or in other words applicable to the performance analysis of diversity combining receivers operating over Nakagami-m fading channels, is presented in closed form in terms of Meijer G-function and Fox H?-function for integer valued fading parameters and non-integer valued fading parameters, respectively. Further analysis, particularly on bit error rate via PDF-based approach, too is represented in closed form in terms of Meijer G-function and Fox H?-function for integer-order fading parameters, and extended Fox H?-function (?) for non-integer-order fading parameters. The proposed results complement previous results that are either evolved in closed-form, or expressed in terms of infinite sums or higher order derivatives of the fading parameter m. © 2012 IEEE. © 2012 Elsevier B.V., All rights reserved.
2012 IEEE 13th International Workshop on Signal Processing Advances in Wireless Communications, SPAWC 2012 -- Cesme -- 93088
Keywords: binary modulation schemes; bit error rate (BER); cellular mobile radio systems; diversity; Extended Fox H?-function (?) distribution; Fox H?-function distribution; Fox H-function distribution; Gamma variates; maximal ratio combining (MRC); Meijer G-function distribution; non-integer parameters